Respon Pertumbuhan dan Hasil Kentang (Solanum tuberosum L.) Varietas Granola dan Desiree terhadap Pemberian Jenis Mulsa Organik Berbeda - Tarigan, Yoshua Aurelio; Rai, I Nyoman; Dharma, I Putu (Nandur, 2021)
Growth Response and Production of Potato ( Solanum tuberosum L.) Granola and Desiree Varieties to Different Types of Organic Mulch. Mulch is a plant cover material, The application of different types of organic mulch will have different effects on increasing land and plant productivity. This research aimed to determine the effect of mulch on the growth and yield of potato, and to determine the interaction between types of mulch and varieties on growth and yield of potatoes. This research was held in Partibi Tembe Village, Karo Regency, North Sumatra Province, starting from January to May 2021. The experiment conducted using a randomized block design (RBD) with two treatment factors. The first factor was potato varieties as the main plot consist of 2 levels i.e. Granola and Desiree, and the second factor was mulching as a subplot consist of 3 levels i.e. without mulch/controle, mulching with ‘Tankos’ and mulching with rice husk. The research showed combination of granola varieties and tankos mulch gave the highest diameter per tuber with a size of 6.63 cm. Provision of tankos mulch significantly increased plant height and weight per tuber, plant height increased by 4.48% compared to rice husks and weight per tuber increased by 21.39% compared to no mulch. Provision of granola varieties in increasing the growth of potato plants. Granola varieties increase the number of primary branches per plant. The desiree variety increased the leaf area of the plant, an increase of 7.57% compared to the granola variety. Granola variety can increase potato yields, indicated by the weight of tubers per plant and weight per tuber, the number of primary branches per plant increased 9.29% compared to the desiree variety, the weight of tubers planted increased by 60.67% compared to desiree variety, and weight per tuber increased by 55.89% compared to desiree.